Browsing Patterns of White-Tailed Deer Following Increased Timber Harvest and a Decline in Population Density - Shawn M. Crimmins; John W. Edwards; W. Mark Ford; Patrick D. Keyser; James M. Crum (International Journal of Forestry Research)
We examined browsing patterns of white-tailed deer (Odocoileus virginianus) on a site in the central Appalachians that experienced a substantial (>50%) reduction in deer population density and an increase in the amount of timber harvest since 2001. We sampled woody browse in and immediately adjacent to 12 clearcuts ranging in age from 0–5 years postharvest in summer 2007. Clearcut-interior areas had higher woody browse abundance and browsing rates than clearcut-edge or mature forest areas. Woody browse abundance was slightly higher within individual clearcuts than in 2001 at higher population densities and lower timber harvest rates. Overall browsing rates declined from approximately 17% in 2001 to less than 5% during our study, suggesting that the combination of deer population control, and increasing the amount of timber harvest across the landscape can reduce herbivory to levels that may not impede growth and survival of forest vegetation.